2019
DOI: 10.3390/ijms20061312
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Understanding the Physiological and Molecular Responses of Populus to Salt Stress

Abstract: Salt stress (SS) has become an important factor limiting afforestation programs. Because of their salt tolerance and fully sequenced genomes, poplars (Populus spp.) are used as model species to study SS mechanisms in trees. Here, we review recent insights into the physiological and molecular responses of Populus to SS, including ion homeostasis and signaling pathways, such as the salt overly sensitive (SOS) and reactive oxygen species (ROS) pathways. We summarize the genes that can be targeted for the genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 114 publications
0
34
0
3
Order By: Relevance
“…Zhang et al [15] presented a review about the physiological and molecular responses of Populus sp. to salinity.…”
Section: Physiological and Biochemical Mechanismsmentioning
confidence: 99%
“…Zhang et al [15] presented a review about the physiological and molecular responses of Populus sp. to salinity.…”
Section: Physiological and Biochemical Mechanismsmentioning
confidence: 99%
“…2007; Feng et al, 2017). Zhang et al (2019) suggested that Populus alba could be used as a model species for understanding salt stress tolerance because of the great variability of salt tolerance within this species. The variability of white poplar genotypes in salt tolerance was confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Досадашња истраживања односила су се на утицај различитих концентрација NaCl на различитим биљним врстама у in vitro условима (S o t i ro p o u l o s et al., 2006;Sotiropoulos, 2007;Feng et al, 2017). Zhang et al (2019) наводе да се Populus alba L. може користити као модел врста за разумевање толератности према стресу соли због велике варијабилности на толерантност према заслањености унутар ове врсте. Варијабилност генотипова беле тополе према толерантности на заслањеност потврђена је и у овом раду.…”
Section: дискусијаunclassified
“…The prevalence and impact of high salinity on plant growth and productivity have drawn increasing attention (Widodo et al, 2009;Zhu et al, 2016;Yang and Guo, 2018). Populus is an economically and ecologically important perennial woody plant that is widely cultivated in the Northern Hemisphere because of their rapid growth and high biomass yields, with marked economic benefits and applications in the production of biofuels, pulp, paper, and other bio-based products, such as chemicals and adhesives (Sannigrahi et al, 2010;Meng and Wu, 2018;Zhang X. N. et al, 2019). However, soil salinization is an increasingly serious threat that limits poplar growth and afforestation program, so breeding salttolerant poplar has become very important and necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The application of genetic engineering and transformation technology provides effective means of improving salt tolerance of poplar by introducing known salt-responsive genes into Populus (Jansson and Douglas, 2007;Li et al, 2009;Su et al, 2011;Ye et al, 2011;Zhou et al, 2014;Yao et al, 2017;Zhang X. N. et al, 2019). Many studies have shown that inroducing transcription factors (TFs) genes into plants is generally more efficient than structural genes, because TFs usually regulate the expression of many target genes in related pathways, leading to enhanced stress torlance in plants (Mcgrath et al, 2005;Li et al, 2009;Su et al, 2011;Licausi et al, 2013;Karim et al, 2015;Yao et al, 2016;Wei et al, 2017;Charfeddine et al, 2019;Zhang C. H et al, 2019;Zhang X. N. et al, 2019;Chen et al, 2020;Jiang et al, 2020). Ethylene responsive factors (ERFs), which have a characteristic AP2/ERF DNA-binding domain, comprise one of the largest TF families in plants (Riechmann et al, 2000;Nakano et al, 2006;Licausi et al, 2013;Zhang X. N. et al, 2019;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%